Civil Servants' Perception on Science Delivery of Private and Public Elementary Schools in Ogun State, Nigeria - J.O. Oni (University of Sofia, 2011)
This study examines civil servants' perception on service delivery of private and public elementary schools in Ogun State, Nigeria. It employs descriptive design of survey type. Purposeful stratified and simple random sampling techniques were used to select 600 respondents among teachers, medical practitioners and local government employees from four out of the state's twenty local government councils. Four (two in one) hypotheses were generated and tested at 0.05 significant level. Self developed questionnaire was used to generate data and student t-test (independent) statistical tool employed for the analysis. The findings revealed, among other things, that gender, age and social-economic status had no significant influence on the perception of civil servants on the service delivery of public and private elementary schools. Level of education, however, significantly influenced civil servants' perception on the service delivery of private elementary schools, whereas it did not affect their perception on service delivery of public elementary schools. Private schools were perceived to be better in the measured indices of service delivery. Government was advised to ensure adequate provision of resources in public schools and thorough supervision of public and private schools so that whichever a parent sends his children will be a matter of choice.